2009 IEEE 8th International Conference on ASIC 2009
DOI: 10.1109/asicon.2009.5351361
|View full text |Cite
|
Sign up to set email alerts
|

A 760mV CMOS voltage reference with mobility and subthreshold slope compensation

Abstract: A low voltage MOSFET-only voltage reference using body effect and subthreshold operation is proposed in this paper', A temperature coefficient of5 ppm/ 'Cfrom -55 'C to 90 'C is achieved as the combined effects of: 1) a suppression of the temperature dependence of mobility; 2) a piecewise compensation of the temperature dependence of subthreshold slope parameter during the second half of temperature range. The voltage reference is designed in SMIC 0.13um CMOS process. It is able to operate at power supply volt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The temperature behavior of I re f is a function of the temperature behavior of parameters µ, V T and η. Referring to the work published in [26], the mobility parameter µ decreases with increasing temperature while the thermal voltage V T and the subthreshold slope η, increases with increasing temperature [25,27]. Thus, it can be concluded that the dominance of the terms η and V T in (7) will will introduce the PTAT temperature dependence in it.…”
Section: Resistor-less Beta Multiplier Circuitmentioning
confidence: 96%
See 1 more Smart Citation
“…The temperature behavior of I re f is a function of the temperature behavior of parameters µ, V T and η. Referring to the work published in [26], the mobility parameter µ decreases with increasing temperature while the thermal voltage V T and the subthreshold slope η, increases with increasing temperature [25,27]. Thus, it can be concluded that the dominance of the terms η and V T in (7) will will introduce the PTAT temperature dependence in it.…”
Section: Resistor-less Beta Multiplier Circuitmentioning
confidence: 96%
“…The threshold voltage, i.e., Part (a), will exhibit CTAT behavior [26]. The temperature behavior of Part (b) is governed by the combined thermal behavior of the thermal voltage V T (0.085 mV/ • C) [25], the subthreshold slope parameter η [27], the mobility factor µ [26] and I 1 which is mirrored from I re f (see Figure 2). The thermal behavior of Part (b) can be predicted from the schematic-level simulation results, as shown in Figure 4.…”
Section: Temperature Sensing Corementioning
confidence: 99%